2001
DOI: 10.1073/pnas.98.3.1047
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular responses of the uterus to embryo implantation can be elicited by locally applied growth factors

Abstract: The implantation of a blastocyst into a receptive uterus is associated with a series of events, namely the attachment reaction followed by decidualization of the stroma. Previous studies established that the gene encoding heparin-binding EGF-like growth factor (HB-EGF) is expressed in the luminal epithelium solely at the site of blastocyst apposition preceding the attachment reaction. We report here the expression during implantation of 21 genes encoding other signaling proteins, including those belonging to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
306
1
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 331 publications
(319 citation statements)
references
References 38 publications
5
306
1
7
Order By: Relevance
“…We also found that downstream of LPA 3 , Bmp2/Wnt4 signaling (Table 2 and Fig 4A) was activated. Bmp2 and Wnt4 are well‐known decidual factors acting downstream of HB‐EGF signaling (Paria et al , 2001; Lee et al , 2007; Franco et al , 2011; Li et al , 2013; Large et al , 2014). Interestingly, a significant negative correlation of gene expression profiles was observed between T13‐injected uteri and uteri null for either Egfr (a target of HB‐EGF), Bmp2, and Wnt4 (Large et al , 2014; Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that downstream of LPA 3 , Bmp2/Wnt4 signaling (Table 2 and Fig 4A) was activated. Bmp2 and Wnt4 are well‐known decidual factors acting downstream of HB‐EGF signaling (Paria et al , 2001; Lee et al , 2007; Franco et al , 2011; Li et al , 2013; Large et al , 2014). Interestingly, a significant negative correlation of gene expression profiles was observed between T13‐injected uteri and uteri null for either Egfr (a target of HB‐EGF), Bmp2, and Wnt4 (Large et al , 2014; Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
“…The signaling required for proper decidualization is generated through two types of cell–cell interactions, i.e., embryo‐epithelial and epithelial–stromal interactions. Maternal factors such as heparin‐binding epidermal growth factor (HB‐EGF) and cyclooxygenase‐2 (COX‐2) are induced in the epithelium surrounding the embryos (embryo‐epithelial interaction) and then act on the stroma to induce the expression of bone morphogenic protein 2 (Bmp2) and wingless‐related MMTV integration site 4 (Wnt4) in stroma (epithelial–stromal interaction; Lim et al , 1997; Paria et al , 2001; Song et al , 2002; Wang et al , 2004; Xie et al , 2007; Large et al , 2014). Mice in which these maternal factors (HB‐EGF, COX‐2, Bmp2, and Wnt4) are knocked out showed obvious defects in decidual reactions (Lim et al , 1997; Wang et al , 2004; Lee et al , 2007; Xie et al , 2007; Franco et al , 2011; Li et al , 2013; Large et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the pregnant ones, the uteri and placentas (if have) were collected at 1300-1400 h on gestational days 1, 2, 3, 4, 13, 20 and one day after delivery, respectively. On gestational day 4 when implantation just occurred, the uteri were collected as the implantation sites and the inter-implantation sites after venous injection of Evans blue dye (1% in saline) at 2200-2300 h [17]. Another forty mice were subjected to ovariectomies, and two weeks later, the mice were randomly divided into four groups.…”
Section: Animal Treatment and Tissue Collectionmentioning
confidence: 99%
“…BMP-2 is involved in blastocyst implantation and cavity formation during gastrulation [Coucouvanis and Martin, 1999;Paria et al, 2001]. BMP-4 heterozygous null mutant mice exhibit abnormalities in the kidney/ureter morphogenesis, including among others, hypo/dysplasia of the kidneys, hydroureters etc.…”
Section: Introductionmentioning
confidence: 99%